MENINGKATKAN KEMAMPUAN KOORDINASI GERAK MATA DAN TANGAN MELALUI MEDIA WIRE GAME BAGI ANAK TUNAGRAHITA RINGAN DI SLB PERWARI PADANG - Fajrin - Sarly (Universitas Negeri Padang, 2013)
This study originated from the observation that researchers carried out in school, that the child's mild mental retardation X has difficulties in eye movement and hand coordination. From the observation, the child has not been able to put mute-mute, both in terms of entering mute-mute to mute the strings to move to follow the strings muted. Based on this research aims to improve coordination of eye and hand movements in installing child mute-mute and see if the wire game media can overcome these problems. This research uses experimental research in the form of Single Subject Research (SSR), the research design is to use design A - B and data analysis techniques using visual analysis chart. The subject was a mild mental retardation children X. Results of this study shows that children's ability to put up ten mute-mute can be enhanced through the wire game media. Baseline condition (A) is performed seven times with the percentage 30%. Intervention condition (B) conducted eleven meetings and increase the ability of child with mental retardation highest percentage of 100%. Concluded that the wire game media can improve eye and hand movement coordination in child mild mental retardation Perwari SLB class II in Padang. Related to the results of research to help improve the ability in coordinating eye and hand movements mild mental retardation children properly, it is recommended that the school especially the teachers to use the media game wire to the ability to coordinate eye and hand movements are more